Evaluating the quality of the Digital Elevation Models produced from ASTER stereoscopy for topographic mapping in the Brazilian Amazon Region - Cleber G. de Oliveira; Waldir R. Paradella (Anais da Academia Brasileira de Ciências, 2009)
Brazilian Amazon is a vast territory rich in natural renewable and non-renewable resources. Due to the adverse environmental condition (rain, cloud, dense vegetation) and difficult access, topographic information is still poor, and when available needs to be up-dated or remapped. In this paper, the feasibility of using elevation generated from orbital ASTER- stereo-pairs images for topographic mapping was investigated for the mountainous relief in the Serra dos Carajás, Pará. The quality of information derived from these optical images was evaluated regarding field altimetric measurements. Precise topographic field information acquired from Global Positioning System (GPS) was used as Ground Control Points (GCPs) for the modeling of the stereoscopic Digital Elevation Models (DEMs) and as Independent Check Points (ICPs) for the calculation of elevation accuracies. The analysis was performed following two approaches: (1) the use of Root Mean Square Error (RMSE) and (2) calculations of trend analysis and accuracy. The investigation has shown that the altimetric accuracy from ASTER fulfilled the Brazilian Map Accuracy Standards elevation requirements for 1:100,000 A Class. In addition, ASTER can provide up-dated planimetric information that is also necessary for cartographic production. Thus, when the environment condition allows the acquisition of stereo-pairs, the use of ASTER can be considered an alternative for semi-detailed topographic mapping in similar environments of the Brazilian Amazon. A Amazônia Brasileira é um rico e vasto território em recursos naturais renováveis e nãorenováveis. Devido às condições ambientais adversas (chuvas, nuvens, vegetação densa) e difícil acesso, a informação topográfica ainda é escassa, e quando disponível necessita ser atualizada ou remapeada. Neste trabalho, a viabilidade de usar elevação para mapeamento topográfico por meio de imagens estereoscópicas orbitais ASTER foi investigada para relevo montanhoso na Serra dos Carajás, Pará. A qualidade da informação produzida destas imagens ópticas foi avaliada considerando medidas altimétricas de campo. Informações topográficas precisas de campo, adquiridas a partir do Sistema de Posicionamento Global (GPS), foram usadas como Pontos de Controle no Terreno (GCPs) para a modelagem de Modelos Digitais de Elevação (DEMs) estereoscópicos e como Pontos de Verificação Independentes (ICPs), para o cálculo das precisões em elevação. As análises foram realizadas seguindo duas abordagens: (1) a utilizaçãodo Erro Médio Quadrático (RMSE) e (2) cálculo das análises de tendência e precisão. A investigação mostrou que a acurácia altimétrica do ASTER atendeu aos requisitos altimétricos para a Classe A 1:100.000 do Padrão de Exatidão Cartográfico. Além disso, dados ASTER podem fornecer informação planimétrica atualizada que também é necessária para a produção cartográfica. Assim, quando as condições ambientais permitem a obtenção de estéreopares, o uso do imageamento ASTER pode ser considerado uma alternativa valiosa para mapeamento topográfico de semi-detalhe em ambientes similares da Amazônia Brasileira.